2022
DOI: 10.3389/fonc.2022.1006114
|View full text |Cite
|
Sign up to set email alerts
|

Natural products exert anti-tumor effects by regulating exosomal ncRNA

Abstract: Currently, more than 60% of the approved anti-cancer drugs come from or are related to natural products. Natural products and exosomal non-coding RNAs (ncRNAs) exert anti-cancer effects through various regulatory mechanisms, which are of great research significance. Exosomes are a form of intercellular communication and contain ncRNAs that can act as intercellular signaling molecules involved in the metabolism of tumor cells. This review exemplifies some examples of natural products whose active ingredients ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 148 publications
0
5
0
Order By: Relevance
“…Chemoresistance hinders the growth of health. Chemotherapeutic drug exposure produces an increase in cancer-associated fibroblast exosomes expressing the microRNA miR-146a (CAFs) [ 109 111 ]. Thereafter, recipient epithelial cells are encouraged to produce the chemo-resistant protein Snail, which enhances cell proliferation and drug resistance.…”
Section: Functionmentioning
confidence: 99%
“…Chemoresistance hinders the growth of health. Chemotherapeutic drug exposure produces an increase in cancer-associated fibroblast exosomes expressing the microRNA miR-146a (CAFs) [ 109 111 ]. Thereafter, recipient epithelial cells are encouraged to produce the chemo-resistant protein Snail, which enhances cell proliferation and drug resistance.…”
Section: Functionmentioning
confidence: 99%
“…Fan Ruolan and Chen Hailan found that C. rhamnose could bind to rhSTAT3 protein and inhibit STAT3 phosphorylation at the Tyr705 site, with significant anti-CRC activity [ 111 ]. Curcumin, a natural compound derived from natural products of the ginger and tannin families, inhibited the survival of human colon cancer HCT116 cells.…”
Section: Histone Phosphorylation Regulates Crcmentioning
confidence: 99%
“…In recent years, the extraction technology and products of essential oils have also greatly promoted the progress of drug discovery for breast cancer. Through breast cancer clinical experiments, it has been shown that diverse medicinal plant extracts, essential oils and natural bioactive compounds have anti-cancer activities in preclinical breast cancer models [37] In addition, the pharmacometric literature related to the key words of "drug delivery" (2020-2022), "nanoparticle" (2020-2022), "binding " (2020-2022) also generated a lot of articles, which provided research ideas for the development of novel anti breast cancer drugs [38][39][40].…”
Section: Analysis Of Countries and Regions Publishing Papersmentioning
confidence: 99%